The Linguistics of Spoken Communication in Early Modern English Writing Exploring Bess of Hardwick's Manuscript Letters - Marcus, Imogen (New Approaches to English Historical Linguistics, 2018)
This book uses a corpus of manuscript letters from Bess of Hardwick to investigate how linguistic features characteristic of spoken communication function within early modern epistolary prose. Using these letters as a primary data source with reference to other epistolary materials from the early modern period (1500-1750), the author examines them in a unique and systematic way. The book is the first of its kind to combine a replicable scribal profiling technique, used to identify holograph and scribal handwriting within the letters, with innovative analyses of the language they contain. Furthermore, by adopting a discourse-analytic approach to the language and making reference to the socio-historical context of language use, the book provides an alternative perspective to the one often presented in traditional historical accounts of English. This volume will appeal to students and scholars of early modern English and historical linguistics.